A Review of Microvascular Ear Replantation - Jung, Sung Won; Lee, Junsang; Oh, Suk Joon; Koh, Sung Hoon; Chung, Chul Hoon; Lee, Jong Wook (Journal of Reconstructive Microsurgery, 2013)
Microvascular ear replantation is a significant challenge because of the small size of the vessels and the fact that traumatic amputations are frequently avulsed. The zone of trauma is therefore extended and the primary repair of the injured vessel is rendered unlikely. The purpose of this study is to review the literature of ear replantation. A review of the relevant literature that has been published since 1980 revealed 47 cases reported in 37 publications. We present 5 cases from our own experience and analyze a total 52 cases of microvascular ear replantation. The patient's age, sex, degree of amputation, cause of injury, ischemic time, method of arterial and venous anastomosis, complications, any additional outflow used, postoperative medications, the requirement for transfusions, and the number of hospital admission days are described. Successful microvascular ear replantations require anastomosis of the vessels if possible. Rather than a vein graft, primary repair of the vessels, or at least pedicled repair of the artery, should be considered to ensure flap survival. In addition, vein repair should be considered if possible to ensure the secure drainage of blood from the replant. With secure circulation, the replant can survive, resulting in a very satisfactory outcome.
Keywords: ear; traumatic; amputation; replantation